The Role of Energy Consumption and Economic Growth on Carbon Emission- Application of Artificial Neural Network - Sah, Hemant Kumar; Sisodia, Gyanendra Singh; Ahmed, Gouher; Rafiuddin, Aqila; Abidi, Naseem (International Journal of Energy Economics and Policy, 2023)
This paper examines the influence of gross domestic product (GDP) and energy consumption (renewable energy and non-renewable energy) on carbon emissions in European Union (EU) Countries use of panel data from 2000 to 2020. By using Artificial Neural Network (ANN) machine learning computational technique, variables are categorized into input and output parameters. The result from the analyses shows that RMSE values of all variables are significant. Further, the normalized importance obtained from the multilayer perception ANN algorithm highlights the importance of variables and their association. The finding suggests that EU countries should adopt a clean energy strategy and policy for environmental protection without compromising economic growth.